Análise técnica e de custo-benefício do sistema não convencional trifásico a dois fios para a distribuição de energia elétrica em média tensão no meio rural - Kräulich, Leyla (2024)
This Doctoral Thesis presents a technique to support the hypothesis that the Three-Phase Two- Wire (TPTW) system is an excellent economic alternative for rural properties that do not have their electricity needs met by single-phase systems. It is necessary to convert these networks into three-phase systems so that the rural areas can offer new opportunities for economic development. However, the costs of such investments represent a great challenge to be overcome when the topic is the extension of the electric power distribution lines. The proposal contributes to clarifying the choice and sizing of structures, the design parameters capable of impacting on the investment costs of the system presented. In an early assessment, it may seem trivial that the TPTW network offers a lower cost as a result of the reduction in construction elements. However, choosing a distribution system is a task that involves a complex analysis of factors, requiring a comprehensive and unbiased comparison discussed in the Sections of this Thesis. To evaluate the costs involved in the implementation of the system, four main scenarios are examined, which are compared to the conventional three-phase system. Another merit of the study is in raising interest on the subject of repowering Single-Wire Earth Return (SWER) networks to three-phase and how appropriate the TPTW system can be for this purpose. There are no works in the technical literature that compare and discuss the choice of these technologies, especially about the TPTW system, whose technical issues are not yet fully established in the literature. The proposed system brings a new approach to rural electrification that can be adapted to the reality of other countries. An analysis of the conditioning factors for grounding, power quality and protection design is presented. The considerations of these thematic areas are taken into account for the experimental validation of the TPTW system in medium voltage, as well as to complete the cost-benefit analysis. The results of the scenarios corroborate that TPTW is capable of overcoming economic challenges, taking advantage of investments in previous installations, or even bringing three-phase energy to locations that are not yet supplied by centralized generation.